MENTAL HEALTH IN THE QUR'AN PERSPECTIVE AND ITS RELEVANCE WITH CONTEMPORARY ISLAMIC EDUCATION IN INDONESIA - Ali Ali (Tadibia Islamika, 2021)
The objectives to be achieved in the discussion of this thesis are: 1. Analyzing the concept of mental health al-Qur'an perspective. 2. Analyzing the concept of contemporary Islamic education in Indonesia. 3. Analyzing the relevance of al-Qur'an perspectives on mental health with contemporary Islamic education in Indonesia. In this study, the authors used a qualitative approach, an approach that emphasizes his analysis in the deductive and inductive inference process and in the analysis of the dynamics of the relationship between the observed phenomena. From this study, a descriptive data was obtained that illustrates the theory of mental health in the perspective of the Qur'an and its relevance to contemporary Islamic education in Indonesia. The results of this study are to improve the quality of human mentality through Contemporary Islamic education in Indonesia. Implementation is through good deeds such as prayer, dhikr, fasting, zakat, pilgrimage, and ruqyah. In terms of evaluation, it is necessary to introduce moral aspects. From the results of these studies obtained good human mental health through Contemporary Islamic education in Indonesia.